2013
DOI: 10.2174/1874325001307010250
|View full text |Cite
|
Sign up to set email alerts
|

Cement-Implant Interface Contamination: Possible Reason of Inferior Clinical Outcomes for Rough Surface Cemented Stems

Abstract: Background:Shape-closed cemented implants rely on a stronger bond and have displayed inferior clinical outcomes when compared to force-closed designs. Implant contamination such as saline, bone marrow and blood prior to cement application has the potential to affect the cement-implant bond. The consequences of implant contamination were investigated in this study.Methods:Fifty Titanium alloy (Ti-6Al-4V) dowels were separated into ten groups based on surface roughness and contaminant, and then cemented in polyv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…11,24,26,27 When PMMA cement is contaminated with blood, micro-morphological changes to gap and void formation in the surface structure may develop, and shear strength is markedly reduced. 22 In our study, after flexural and compressive strength testing, fractures within the cement mantle consistently occurred in areas of weakness caused by blood laminations, which were not noted before curing and were more prominent after curing to the extent of disrupting the previously smooth cylindrical contour of the specimen (Fig. 2).…”
Section: Discussionsupporting
confidence: 53%
“…11,24,26,27 When PMMA cement is contaminated with blood, micro-morphological changes to gap and void formation in the surface structure may develop, and shear strength is markedly reduced. 22 In our study, after flexural and compressive strength testing, fractures within the cement mantle consistently occurred in areas of weakness caused by blood laminations, which were not noted before curing and were more prominent after curing to the extent of disrupting the previously smooth cylindrical contour of the specimen (Fig. 2).…”
Section: Discussionsupporting
confidence: 53%
“…The ingrowth of cementless components in the postoperative period is important for long-term stability of the implant [29]. Vigorous manipulation of cemented implants might damage the cement-implant interface, with unfavorable consequences for implant survival [30]. In late PJI (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The results from their study are particularly interesting given that bone-cement compositions with antibiotics introduced by the manufacturer are widely used in Europe, whereas in the United States manual antibiotic powder addition to traditional bone cement during surgery is preferred [44]. The authors of other studies [34,45] monitored the formation of gaps and voids in the micromorphological structure of the blood-contaminated cement, whose primary effect is the reduction in the cement shear strength. On the other hand, the test results presented in the study by Graham et al [46] indicated the positive effect of the suitable selection of the cement-mixing method (vacuum vs. manual) on the reduction of porosity, which were found to increase the crack resistance and its cyclic loading strength.…”
Section: Discussionmentioning
confidence: 99%